Images of COVID-19 Infection Cases in Asymptomatic or Paucisymptomatic Patients With Neoplastic Diseases on 18F-FDG PET/CT. (December 2020) - Grellier, Jean-François; Lussato, David; Guernou, Mohamed; Queneau, Mathieu; Bonardel, Gérald
Abstract : Abstract: We describe the results of 18 F-FDG PET/CT of 3 patients referred to our institution during the single day of Monday, March 23, 2020, for an initial assessment of cancer extension or for the therapeutic evaluation of chemotherapy of neoplastic pathology, with no obvious infectious or respiratory symptoms at the time of examination. A retrospective review of the recent clinical history of patients in association with the typical pulmonary images on CT scan suggested the diagnosis of COVID-19. The characteristic aspects of COVID-19 infection should be recognized on 18 F-FDG PET/CT, even if patients are asymptomatic or minimally symptomatic.